Endometrial and vaginal microbiome in donkeys with and without clinical endometritis - Li, Jing; Zhu, Yiping; Mi, Junpeng; Zhao, Yufei; Holyoak, Gilbert Reed; Yi, Ziwen; Wu, Rongzheng; Wang, Zixuan; Zeng, Shenming (Frontiers in Microbiology, 2022)
Endometrial and vaginal microbiomes are critical in the study of endometritis which is an important cause of infertility in donkeys. Our objective was to investigate the difference of the endometrial and vaginal microbiome between healthy donkey jennies (group C) and jennies with endometritis (group E). Endometrial and vaginal swab samples were collected and 16s rRNA gene amplicon high-throughput sequencing technique was applied to identify the microbial composition in the samples. A similar microbial composition pattern was found between endometrial and vaginal samples, which indicated the impact of the vaginal microbiome on the endometrial microbial environment and health. There was a significant difference of endometrial and vaginal swab samples between the two groups. Ruminococcaceae and Lachnospiraceae were significantly more abundant in endometrial and vaginal microbiome of group E than in group C. Their dominance was consistent with increased anaerobic bacterial taxa in the functional analysis, which might be associated with the pathogenesis of endometritis in donkeys. Sphingomonadaceae , a bacterial family reported in bovine semen, was statistically more abundant in endometrial microbiome of group E than in group C, which might suggest an association between high abundance of Sphingomonadaceae possibly due to uncleared semen and donkey endometritis. Our study revealed the composition of the vaginal and endometrial microbiome in healthy and endometritis donkeys. These findings will provide more insight into the pathogenesis of donkey endometritis.